Resettlement and landscape-level conservation: Corridors, human-wildlife conflict, and forest use in Central India. (April 2019) - Neelakantan, Amrita; DeFries, Ruth; Krishnamurthy, Ramesh
Abstract: Since the origin of the protected area network, authorities have resettled people in the interest of wildlife conservation. However, the impacts of resettlement on wildlife corridors connecting increasingly insular protected areas and the interaction of resettlement with existing human-wildlife conflict (HWC) outside of protected areas remain unclear. Using Kanha National Park (KNP) in central India as a case study, we quantified impacts of 450 households (that were resettled from 2009 to 2013, surveyed in 2016) on non-protected forests at their new settlement locations. We measured forest use for cattle grazing, tendu leaf extraction (a commercial non-timber forest product) and consumption of forest foods. We also quantified HWC risks that resettled households face at their new settlement locations. We use published spatial analyses on designation of the corridor and risks of human wildlife conflict in conjunction with our data to assess post-resettlement impacts at the new settlement locations. Overall, most resettled households (330) have moved to existing villages that lie outside of wildlife corridors around KNP. They comprise <10% of existing populations at most of their new settlement villages. Many resettled households and their non-resettled neighbors face high HWC risks due to the spatial patterns of HWC around KNP. Controlling for assets and proximity to forest, resettled households own more cattle, are less involved in tendu trade, and consume fewer forests foods than non-resettled neighbors. Model results suggest that increasing off-farm economic opportunities would reduce pressures on forest resources for both resettled and non-resettled households. Our findings, while limited to the KNP landscape, provide approaches applicable in other human-dominated places to design resettlement strategies towards landscape-level conservation goals. Highlights: Human resettlement can affect habitat connectivity and human wildlife conflict. Most resettled households from Kanha National Park are outside of wildlife corridors. Households in close proximity to protected area face high HWC risks. Resettled households are less involved in tendu trade and consume fewer forest foods. Increasing off-farm economic opportunities would reduce pressures on forests.